Critical Success Factors and Their Impact on Strategic Agility: A Field Study on Banks Operating in Yemen - Gamal Dirhim Ahmed Zaid; Nabil Ali Naji Mohammed Aldemah (University of Science and Technology, Sana’a, Yemen, 2025)
The study aimed to determine the Critical Success Factors (CSFs) in banks operating in Yemen and identify their impact on Strategic Agility (SA). The study followed a descriptive analytical approach and used a questionnaire as a tool to collect data from a relative random sample of (322) individuals selected from a study population of 1,973 employees, representing those working in leadership and supervisory positions in banks operating in Yemen. The number of valid questionnaires for analysis was (281). The findings revealed a statistically significant positive impact of CSFs on SA in Yemeni banks, with varying impacts from the different dimensions of CSFs. The dimensions of (organizational structure and supportive leadership) had the greatest impact, while (organizational culture and information technology) had the least impact, with no impact from the human resources dimension on SA. The findings also indicated that SA, in all its dimensions, was achieved at a high level, and that Yemeni banks practiced CSFs in all their dimensions to a high degree. The study recommended continuing to enhance and develop SA in Yemeni banks by integrating performance evaluation tools and continuous monitoring of various strategic dimensions, with sufficient resources allocated for this purpose. Additionally, it recommended strengthening attention to all CSFs, particularly those which received less attention, such as organizational culture and organizational structure. The study also suggested reevaluating human resources strategies in Yemeni banks to activate their role in enhancing SA.